2020
DOI: 10.3390/md18020106
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological Comparison of Two Isomeric Nicotinic Receptor Agonists: The Marine Toxin Isoanatabine and the Tobacco Alkaloid Anatabine

Abstract: Many organisms possess "secondary" compounds to avoid consumption or to immobilize prey. While the most abundant or active compounds are initially investigated, more extensive analyses reveal other "minor" compounds with distinctive properties that may also be of biomedical and pharmaceutical significance. Here, we present an initial in vitro investigation of the actions of two isomeric tetrahydropyridyl ring-containing anabasine analogs: isoanatabine, an alkaloid isolated from a marine worm, and anatabine, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…4 ) is the second most abundant alkaloid (~4%) present in Nicotiana species. 36 , 48 This alkaloid was first isolated from the leaves of N. tabacum by Spath and Kesztler in 1937, who also established the chemical structure through total synthesis. 49 Anatabine is a pyridine-dihydropyridine structurally related to anabasine.…”
Section: Plant-derivedmentioning
confidence: 99%
See 4 more Smart Citations
“…4 ) is the second most abundant alkaloid (~4%) present in Nicotiana species. 36 , 48 This alkaloid was first isolated from the leaves of N. tabacum by Spath and Kesztler in 1937, who also established the chemical structure through total synthesis. 49 Anatabine is a pyridine-dihydropyridine structurally related to anabasine.…”
Section: Plant-derivedmentioning
confidence: 99%
“… 49 Anatabine is a pyridine-dihydropyridine structurally related to anabasine. 48 Subsequent studies reported that anatabine exists as an 85:15 scalemic mixture of (−)- and (+)-enantiomers in Nicotiana species. 50 …”
Section: Plant-derivedmentioning
confidence: 99%
See 3 more Smart Citations